{(1/3)^-1*(-9)^-1}^-1Solve using exponents. (pls give full method) October 10, 2021 by Ayla {(1/3)^-1*(-9)^-1}^-1 Solve using exponents. (pls give full method)

Law of exponents used :- [tex]x^{-1}[/tex] = [tex]\frac{1}{x}[/tex] [ (1/3)^-1 * (-9)^-1 ]^-1 = [ 3 * -1/9 ]^-1 = [ -3/9 ]^-1 = [ -1/3 ]^-1 = -3 Therefore, your answer is -3. Log in to Reply

Law of exponents used :-[tex]x^{-1}[/tex] =[tex]\frac{1}{x}[/tex]

[ (1/3)^-1 * (-9)^-1 ]^-1= [ 3 * -1/9 ]^-1= [ -3/9 ]^-1= [ -1/3 ]^-1= -3Therefore, your answer is -3.